PENGARUH TEMPERATUR PADA NILAI THDF (TRANSFORMER HARMONIC DERATING FACTOR ) DALAM TRANSFORMATOR DISTRIBUSI - Handajadi, Wiwik (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Based on the previous research it can be seen that the load of a distribution transformer which was sinked in water showed that the THDF value is greater than one, and this is an advantage to optimize the use of the transformer.This research analysed the effects of the increase temperature in load at the transformator distribution. The effects of harmonic were calculated based on the de-crease of the performance of the transformator, i.e. operating capacity of the trafo that is called THDF (The Transformer Harmonic Derating Factor). The results of the experiment showed that the increase of the temperature was not significant to the THDF. The water that was asummed as a cooling media was not true. it was a media to increase the quality of grounding system that can reduce the effect of harmonic in transformator distribution.